2019
DOI: 10.5812/asjsm.92849
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of All-Extremity High-Intensity Interval Training on Plasma Pentraxin 3 in Young Overweight and Obese Women

Abstract: Background: In obese individuals, chronic inflammation is associated with atherosclerosis and cardiovascular diseases. This inflammation may be reduced by anti-inflammatory proteins like pentraxin 3 (PTX3). High-intensity interval training (HIIT) mostly with weight bearing might also alleviate this inflammation. This type of exercise may be limited in obese individuals due to their excessive body mass, muscular weakness or joints pain. Whether non-weight bearing HIIT can increase these anti-inflammatory protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Of these, seven were excluded because they did not use a control group (n = 3), missing information (n = 2), no participants with overweight and obesity (n = 1), and not a RCT (n = 1). There remained 10 studies: three including overweight adults 34 36 , four adults with obesity 37 40 and three adults with overweight and obesity 41 43 . They were all included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, seven were excluded because they did not use a control group (n = 3), missing information (n = 2), no participants with overweight and obesity (n = 1), and not a RCT (n = 1). There remained 10 studies: three including overweight adults 34 36 , four adults with obesity 37 40 and three adults with overweight and obesity 41 43 . They were all included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…As for the intervention, five studies used continuous aerobic training 35 37 , 39 , 40 , two resistance training 34 , 38 , one high-intensity interval training (HITT) 41 , one used both HITT and resistance training 42 , and one used continuous aerobic training and HITT 43 . Table 1 details the study interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sub-study was a part of a project that was designed to evaluate the immunomodulatory effects of various exercise interventions on TLR4 responses in order to recommend the best therapeutic exercise strategy for people with overweight and obesity. The Ethics Committee approved the study (protocol #1596.039), and some findings were previously published (Hovsepian et al, 2019). The study was conducted according to the Declaration of Helsinki guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Significance (p value) Many studies have confirmed that HIIE improves vascular function in obese people, which has been attributed mainly to traditional cardiovascular risk factors (Sawyer et al, 2016;De Lorenzo et al, 2018;Hovsepian et al, 2021;Mendelson et al, 2022). This study analyzed the possible mechanism through which HIIT improves vascular endothelial function from the perspective of WSS.…”
Section: Conditionsmentioning
confidence: 98%